Nilai-Nilai dalam Pendidikan Islam yang Terdapat pada Ayat Al-Qur’an yang Pertama dan Terakhir Kali Diturunkan - Ananda fitria; Nasywa zakiyah; Wita siti maryam (Jurnal Kajian Islam dan Sosial Keagamaan, 2023)
The Islamic teachings included in the first and second Qur'anic verses need to be understood because this is one of the most important things for both teachers and students. This study's goal is to understand the principles of Islamic education found in the first and last verses of the Qur'an. This study employs a qualitative research methodology using library research techniques (studi kepustakaan). The literature review in this work consists of published writings; they include books and articles that have been published in journals. iterature studies like this one go through many steps before reaching their goals, such as verifying that the sources are consistent with the research question, after which the previous literature review is adjusted to the research question, and finally, the literature review is based on sources that are consistent with the research question in order to produce new ideas. The study's findings indicate that there are a few ulama's observations regarding the first and second times that a particular verse is read aloud, as well as the educational principles that are included in each of those verses.